CTIM-13. PHASE 1 CLINICAL TRIAL OF ONCOLYTIC VIRAL IMMUNOTHERAPY WITH CAN-2409 + VALACYCLOVIR IN COMBINATION WITH NIVOLUMAB AND STANDARD OF CARE (SOC) IN NEWLY DIAGNOSED HIGH-GRADE GLIOMA (HGG). (12th November 2021) - Wen, Patrick; Aguilar, Laura; Ye, Xiaobu; Reardon, David; Bi, Wenya Linda; Peruzzi, Pierpaolo; Patel, Nirav; Strowd, Roy; Tatter, Stephen; Lee, Ian; Walbert, Tobias; Snyder, James; et al.
Abstract: BACKGROUND: CAN-2409 is a replication-deficient adenovirus that delivers HSV thymidine kinase to cancer cells, resulting in local conversion of orally administered valacyclovir into a toxic metabolite. Previously, a phase 1b/2 clinical trial of CAN-2409 combined with standard-of-care (SOC) demonstrated safety and improved survival in HGG patients. Addition of CAN-2409 to nivolumab has the potential to activate locally recruited lymphocytes and teach them to recognize tumor neoantigens, changing the 'cold' immunosuppressive tumor microenvironment, and synergizing with the activity mediated by immune checkpoint inhibitors. This notion is supported by preclinical experiments showing that the combination of CAN-2409 with anti-PD1 therapy was more effective than either treatment alone. METHODS: This ongoing phase 1 clinical trial evaluates safety and initial efficacy of CAN-2409 combined with nivolumab and SOC in newly diagnosed HGG. CAN-2409 is injected during neurosurgery into the tumor bed, followed by 14-days of valacyclovir. Radiation starts within 8 (+/-4) days of surgery. Temozolomide is administered to MGMT-methylation positive patients only. Nivolumab is given every 2 weeks, up to 52-weeks. Deep immune profiling studies are ongoing and initial results will be available shortly. RESULTS: From February 2019 to March 2021, 41 patients were enrolled and 35 were evaluable for safety from the combination of CAN-2409, nivolumab and SOC: 24 male and 11 female; 34 glioblastoma, 1 diffuse astrocytoma; 33 IDH-wildtype, 2 IDH-mutant; 15 MGMT-methylated, 20 unmethylated. Median age was 62-years (range 28-79), median KPS 90 (range 80-100). With 13 months median follow-up, no unexpected serious adverse events were observed, and 23 patients are still alive. The most frequent possibly related adverse events (>10%) were nausea, fatigue, fever, headache, and increased ALT. CONCLUSIONS: The combination of CAN-2409 + nivolumab + SOC was well tolerated. Clinical follow-up and extensive biomarker analyses will provide a better understanding of the therapeutic potential of this approach.